Lack of temporal variability in the benthos of a coastal brackish water lagoon in Greece - NICOLAIDOU, A. (Mediterranean Marine Science, 2007)
The benthic fauna was studied in the small, brackish water Mazoma Lagoon in the Amvrakikos bay. Benthic samples were collected at 10 stations at bimonthly intervals over a period of a year. Temperature, salinity, dissolved oxygen and sediment organic carbon were also measured at the same time. The environmental parameters showed the expected seasonal variability but the benthic community, the structure of which was only related to plant biomass, did not. This lack of seasonality is attributed to the continuous reproduction of some abundant species and to species interactions.